Direct Torque Control Strategy for Doubly Fed Induction Machine under Low Voltage Dips - Venu Madhav Gopala; Y. P. Obulesh (Institute of Advanced Engineering and Science, 2012)
This paper proposes a control strategy of generating a rotor flux amplitude reference for Doubly Fed Induction Machine (DFIM) based wind turbines. In addition to that a Direct Torque Control (DTC) strategy that provides fast dynamic response accompanies the overall control of the wind turbine. It is specially designed to address perturbations, such as voltage dips, keeping controlled the torque of the wind turbine, considerably reducing the stator and rotor over currents during faults. Despite the fact that the proposed control does not totally eliminate the necessity of the typical crowbar protection for this kind of turbines, it eliminates the activation of this protection during low depth voltage dips.DOI: http://dx.doi.org/10.11591/ijpeds.v2i4.710